Analysis of Generation Z's Purchase Interest Perception in Using QRIS in Balikpapan City - Sari, Dessy Handa; Khairiyah, Nurul Musfirah; Apriani, Endang Sri; Agustin, Kety Lulu (Universitas Muhammadiyah Pontianak, 2026)
This study examines the impact of QRIS usage on Generation Z’s behavior and purchase intention in Balikpapan. Using a quantitative approach and questionnaire-based data, findings reveal that convenience, understanding, and benefits significantly influence user behavior, which in turn affects purchase intention. Behavior also mediates the relationship between these factors and intention. This research introduces a novel model by integrating understanding into digital transaction studies and highlighting behavior's mediating role. Results emphasize that enhancing users’ perceptions of convenience, understanding, and benefits can foster positive behavior and increase purchase intention in digital payment contexts.